Delayed recovery from severe acute respiratory syndrome coronavirus-2 related anosmia predicts incomplete olfactory restoration. Issue 3 (13th March 2022) - Fernandez, I J; Molinari, G; Federici, G; Silvestri, M; De Corso, E; Presutti, L; Alicandri-Ciufelli, M; Lucidi, D
Abstract: Objective: This study aimed to assess the olfactory recovery rates and patterns in a cohort of coronavirus disease 2019 positive patients, and to investigate the clinical predictors of poor long-term olfactory restoration. Methods: An observational retrospective study was conducted on 146 patients between September 2020 and January 2021 at a tertiary referral hospital. Coronavirus disease 2019 positive patients with olfactory dysfunction were sent a modified version of the COVID-19 Anosmia Reporting Tool for Clinicians via e-mail. Results: The difference in median recovery time between complete recovery and incomplete or no recovery was statistically significant. On multivariate analysis, the only significant factor associated with incomplete or no recovery was anosmia duration. Conclusion: After a mean time of 5.6 months from severe acute respiratory syndrome coronavirus-2 infection, persistent olfactory disorders were self-reported in 36.7 per cent of patients. Complete recovery was more likely to occur within 15 days. Given the high prevalence of coronavirus disease 2019, a large number of patients are expected to suffer from long-term olfactory morbidity.